2015
DOI: 10.1007/s00590-015-1727-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with pars defects identified in adulthood

Abstract: Approximately 90 % of patients with terminal-stage spondylolysis that was first diagnosed in adulthood involved the L5. Also, about 40 % had no history of athletic activity or experience of LBP during their growth period. In addition, only some patients with L5 spondylolysis had SBO, and all but one of these patients was male. This suggests that male patients with L5 spondylolysis may have some congenital predisposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The risk factors for non-union in the patients with lumbar spondylolysis are multifactorial. Sakai et al [25] reported that patients with L5 spondylolysis and spina bifida occulta have predisposing factors in the development of terminal-stage spondylolysis. In order to analyze the detail of the correlation between the CR and bone union, we need to conduct studies on a larger sample in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for non-union in the patients with lumbar spondylolysis are multifactorial. Sakai et al [25] reported that patients with L5 spondylolysis and spina bifida occulta have predisposing factors in the development of terminal-stage spondylolysis. In order to analyze the detail of the correlation between the CR and bone union, we need to conduct studies on a larger sample in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, about 90% of end-stage L5 spondylolysis patients are first diagnosed in adulthood. In addition, about 40% of cases had no sports history or low back pain experience in their growth period[ 12 ]. If patients with lumbar spondylolysis have low back pain, conservative treatment is ineffective, or imaging shows spondylolisthesis, surgical treatment is required[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…SBO is caused by failure of fusion between posterior vertebral elements without affecting the spinal cord or meninges. It is usually observed at L5 and/or at the upper one or lower two sacral vertebrae [1,2]. Goto et al reported a case of SBO at the thoracolumbar junction and estimated the incidence as <5% within all SBO patients [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Spina bifida occulta (SBO) is a common malformation of the lamina of the spine, most commonly occurring in the sacrum or lower lumbar spine [1,2]. Spondylolysis is a common etiology of back pain in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%